"Justification by faith" in Luther and "the people of Alliance" in Sanders: a new hermeneutics for the Law´s Israel - Zitzke, Ângela (2011)
This article has the objective of working with the concept of justification through the apostle Paul's theology. At first, it's necessary understand the justification as a God's first act and that justification is mediated by his grace, through faith. In a second moment, it will speak about justification in Luther as a reaction to the christian model, where the christian only work because he is motivated by the grateful love generated in his heart. In a third time, this article will deconstruct the interpretation from the reformers of the 16th Century, where Israel is interpreted as the people of the Law. Authors such as SANDERS and DUNN assert that, since the principles, Israel was a religion of grace through the Covenant that God had made with his people.